2015
DOI: 10.1007/s10648-015-9310-x
|View full text |Cite
|
Sign up to set email alerts
|

Not New, but Nearly Forgotten: the Testing Effect Decreases or even Disappears as the Complexity of Learning Materials Increases

Abstract: The testing effect is a finding from cognitive psychology with relevance for education. It shows that after an initial study period, taking a practice test improves long-term retention compared to not taking a test and-more interestingly-compared to restudying the learning material. Boundary conditions of the effect that have received attention include the test format, retrieval success on the initial test, the retention interval, or the spacing of tests. Another potential boundary condition concerns the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
88
2
15

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(111 citation statements)
references
References 75 publications
6
88
2
15
Order By: Relevance
“…However, this is not always an advantage as it can encourage an instrumental approach to testing where the student learns in order to pass the test rather than to learn skills that will be relevant in a wider context. The testing effect, whereby the act of being tested not only assesses learning but enhances later long-term retention, is recognised (Roediger & Karpicke, 2006), though this effect decreases as the complexity of the material increases (Van Gog & Sweller, 2015). The use of adaptive quizzes can also encourage assessment design to focus on objective knowledge rather than the development of process skills.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is not always an advantage as it can encourage an instrumental approach to testing where the student learns in order to pass the test rather than to learn skills that will be relevant in a wider context. The testing effect, whereby the act of being tested not only assesses learning but enhances later long-term retention, is recognised (Roediger & Karpicke, 2006), though this effect decreases as the complexity of the material increases (Van Gog & Sweller, 2015). The use of adaptive quizzes can also encourage assessment design to focus on objective knowledge rather than the development of process skills.…”
Section: Introductionmentioning
confidence: 99%
“…The testing effect occurs when people, having memorized some information and being tested on that information, perform better on a subsequent test than people who have been asked to relearn the information (for reviews, see Roediger, Putnam, & Smith, ; van Gog & Sweller, ). The effect has been demonstrated by using instructional content composed of animations (Johnson & Mayer, ), prose passages (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, like all instructional effects, it has limits. In the experiments of this paper, we investigated the suggestion that the effect is more likely using low complexity information that needs to be memorized rather than higher complexity information that requires more complicated processing and additional working memory resources (van Gog & Sweller, ). We will begin by relating the testing effect to the worked example effect that normally uses complex information.…”
Section: Introductionmentioning
confidence: 99%
“…While this may maximize the measurable effects of testing, it is also less educationally relevant, because the test items can be memorized and it requires no transfer of the material to a different context. In support of this, Gog and Sweller (2015) found that the testing effect disappears as the complexity of the material increases. In this study, we did not re-use assessment items, so no participant was exposed to an assessment item more than once.…”
Section: Lack Of a Testing Effectmentioning
confidence: 78%
“…Although the testing effect has been replicated in laboratory studies with educationally-relevant materials, classroom-based studies produce effect sizes that are typically smaller than those in simple, repeated testing memorization tasks (Gog & Sweller, 2015;Roediger & Karpicke, 2006).…”
Section: Background the Testing Effectmentioning
confidence: 99%